Aerogel thermal insulation waterproof mortar and preparation method thereof

CN121800475BActive Publication Date: 2026-10-27JIANGSU OUXIDUN TECH CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202512025727.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2025-12-30
Publication Date
2026-10-27
Estimated Expiration
2045-12-30

AI Technical Summary

Technical Problem

这类材料存在诸多固有缺陷:首先,轻质骨料内部多为开孔结构,自身强度低,在砂浆搅拌和施工过程中易破损,导致保温性能下降;其次,这些开孔结构会大量吸附并迁移水分,致使成品砂浆干密度大、吸水率高

Benefits of technology

一、本发明通过独创的"等离子体活化-有机硅疏水改性"、"钛酸酯偶联剂界面桥接"、"球磨复合构建导热通路"三级预处理工艺,在分子层面构建了稳定的多相界面结构。等离子体处理使气凝胶表面产生丰富的活性位点,显著提高了有机硅防水剂的接枝密度和结合强度,形成耐久性超疏水界面;钛酸酯偶联剂在沥青胶粉表面引入的活性基团,能与水泥水化产物形成牢固的Si-O-Si和Si-O-Ca共价键合;球磨复合使碳纳米管与相变微胶囊形成稳定的"核-壳"导热结构。这种多级协同的功能网络突破了传统材料中各组分的性能制约,实现了保温、防水、力学性能的协同优化。

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The application discloses aerogel heat-insulation waterproof mortar and a preparation method thereof. The mortar is composed of cement, hydrophobic aerogel, interface modified asphalt glue powder, composite phase change heat-conducting material, blast furnace slag powder, silica fume, nano montmorillonite, titanium dioxide aerogel powder, expanded vermiculite, shape memory polymer emulsion, chitosan, biochar powder, carbon fiber, basalt fiber and the like. The preparation method comprises the following steps: obtaining the hydrophobic aerogel by modifying through plasma treatment and cooperating with an organic silicon waterproof agent; modifying the interface of the asphalt glue powder by adopting a titanate coupling agent; constructing a phase change microcapsule-carbon nanotube heat-conducting network by ball milling; forming a basic framework by adopting a hierarchical mixing process and then introducing functional components; and finally realizing the cross-linking and solidification of the shape memory polymer and the chitosan by ultrasonic assistance and program temperature control. The mortar prepared by the application realizes multifunctional integration, and effectively solves the technical problems of single performance and poor durability of traditional heat-insulation materials.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of building materials technology, specifically, it relates to an aerogel thermal insulation and waterproof mortar and its preparation method. Background Technology

[0002] Building energy conservation is the core driver of green building development, placing higher demands on the comprehensive performance of exterior wall insulation systems. Ideal exterior wall insulation materials not only need to possess excellent thermal insulation performance, but also must be firmly bonded to the building substrate and have reliable waterproof and seepage-resistant capabilities to cope with complex and ever-changing external environments.

[0003] Currently, traditional thermal insulation mortars mostly use cement as the base material, combined with lightweight aggregates such as expanded perlite and vitrified microspheres. These materials have several inherent drawbacks: First, the lightweight aggregates often have an open-cell structure with low inherent strength, making them prone to breakage during mortar mixing and construction, leading to decreased insulation performance. Second, these open-cell structures absorb and migrate large amounts of moisture, resulting in high dry density and water absorption in the finished mortar. In high-humidity or freeze-thaw cycles, the absorbed moisture not only significantly increases the material's thermal conductivity, causing a sharp decline in insulation performance, but also easily leads to durability problems such as hollowing, cracking, and even detachment. Furthermore, the waterproofing performance of traditional mortars largely relies on the application of silicone waterproofing agents to the surface after molding. This "external" waterproofing strategy struggles to form a complete, continuous, and durable hydrophobic barrier within the material and its capillary pores, often resulting in a waterproofing lifespan that does not match the structural lifespan.

[0004] Silica aerogel, due to its unique nanoporous network structure and extremely low solid-state thermal conductivity (often below 0.020 W / (m·K)), is hailed as one of the most promising new thermal insulation materials. However, its direct application to cement-based mortar systems faces two major technical bottlenecks: First, the nanoscale skeleton structure of aerogel has low mechanical strength and is very fragile. During conventional dry and wet mixing processes, it is prone to collapse and pulverization due to mechanical shear forces, resulting in the complete loss of its excellent theoretical thermal insulation performance in actual products. Second, unmodified aerogel exhibits significant hydrophilicity and actively absorbs environmental moisture. This not only exacerbates the potential risk of structural damage but also fundamentally contradicts the waterproof and seepage-resistant functions sought by mortar systems.

[0005] To improve the flexibility and crack resistance of mortar, asphalt powder prepared from waste tires has attracted attention as a low-cost material that combines elasticity and inherent hydrophobicity. However, when this organic, hydrophobic asphalt powder is combined with inorganic, high-specific-surface-area aerogels and highly polar cement hydration products, a severe interfacial compatibility challenge is encountered. The significant differences in physicochemical properties among the components mean that simple physical mixing results in weak interfacial bonding, which easily becomes stress concentration points and preferred pathways for water penetration. This not only fails to achieve the synergistic effect of insulation, waterproofing, and flexibility, but may also lead to overall performance degradation due to interfacial defects.

[0006] Most importantly, building envelopes are subjected to cyclical thermal stresses caused by diurnal and seasonal temperature fluctuations during actual use, which is a major cause of cracking and delamination in insulation systems. Existing insulation mortars are passive and lack the ability to adaptively adjust to temperature changes. While phase change materials (PCMs) can absorb or release latent heat through a phase change process to smooth temperature fluctuations, their application in mortar faces bottlenecks: direct introduction of PCMs leads to leakage, poor compatibility with cementitious matrices, and severe degradation of the material's mechanical strength. Therefore, how to organically combine phase change temperature control with insulation and waterproofing systems, and overcome its negative effects, has become a key challenge.

[0007] In summary, there is an urgent need in this field for an innovative, systematic solution. This solution cannot be a simple aggregation of existing technologies, but must start from the levels of molecular interface engineering and material structure design. Through innovative pretreatment processes and precise manufacturing procedures, it should simultaneously address core issues such as the structural protection and durable hydrophobicity of aerogels, the interfacial chemical coupling of asphalt powder, and the functional encapsulation and efficient thermal conductivity of phase change materials. This will proactively construct a stable composite system with strong and tough bonding of all components and synergistic functional enhancement, ultimately achieving an integrated breakthrough in multiple properties such as thermal insulation, waterproofing, temperature regulation, and load-bearing capacity. Summary of the Invention

[0008] To address the aforementioned technical problems, this invention provides an aerogel thermal insulation and waterproof mortar and its preparation method.

[0009] To achieve the above objectives, the technical solution provided by the present invention is as follows: A method for preparing an aerogel thermal insulation and waterproof mortar includes the following steps: (1) Place 5-20 parts of hydrophilic silica aerogel in a plasma treatment device, and treat it at 500-800W power for 5-15 minutes under an argon atmosphere and a pressure of 50-100Pa. Then, spray in 10-20% of the aerogel mass of organosilicon waterproofing agent and treat it at a speed of 200-400rpm for 10-20 minutes to obtain hydrophobic aerogel. The organosilicon waterproofing agent is a mixed solution of methyltrimethoxysilane and hexamethyldisilazane in a mass ratio of 2:1. (2) Preheat 5-15 parts of 40-80 mesh waste tire asphalt powder to 70-90℃, add 2-4% of titanate coupling agent NDZ-201 by weight of the powder, and react at 400-600 rpm for 20-40 min to obtain interface modified asphalt powder. (3) Grind 5-15 parts of phase change microcapsules and 3-8 parts of carbon nanotubes together in a ball mill at a speed of 300-500 rpm for 30-60 min to obtain a composite phase change thermal conductive material; the core material of the phase change microcapsules is paraffin wax, the phase change temperature is 22-28℃, and the shell material is polymethyl methacrylate. (4) Grind 30-50 parts of cement, 15-25 parts of blast furnace slag powder, 10-20 parts of silica fume, 5-15 parts of nano montmorillonite, 5-10 parts of titanium dioxide aerogel powder, and 3-8 parts of expanded vermiculite together to 300-400 mesh to obtain inorganic composite matrix. (5) The inorganic composite matrix obtained in step (4), the interface-modified asphalt powder obtained in step (2), 2-8 parts of reinforcing fiber, and 3-9 parts of biochar powder are mixed at a speed of 400-600 rpm for 10-20 minutes to form a basic skeleton material; the reinforcing fiber is a hybrid fiber system composed of carbon fiber with a length of 2-5 mm and basalt fiber with a length of 1-3 mm in a mass ratio of (1.5-2.5):1. (6) Add the hydrophobic aerogel obtained in step (1), the composite phase change thermal conductive material obtained in step (3), 2-6 parts of redispersible latex powder, and 3-7 parts of hydroxypropyl methylcellulose ether to the basic skeleton material obtained in step (5), and mix at 100-200 rpm for 15-25 min to obtain a uniform dry mix. (7) Prepare a liquid phase by mixing 50-70 parts of water, 1-3 parts of polycarboxylate superplasticizer, 2-5 parts of water-retaining agent, 10-20 parts of shape memory polymer emulsion, and 3-8 parts of chitosan; add the liquid phase to the dry mixture obtained in step (6) at a speed of 40-80 rpm under the assistance of ultrasound at a frequency of 20-40 kHz and a power of 200-400 W, and then heat it to 60-70 ℃ at a speed of 2-4 ℃ / min, and stir it continuously at a speed of 100-150 rpm for 20-40 min at this temperature to obtain the aerogel thermal insulation and waterproof mortar; the shape memory polymer emulsion is a polyurethane emulsion with a glass transition temperature of 25-35 ℃.

[0010] Furthermore, in step (1), the plasma treatment and the modification of the organosilicon waterproofing agent work synergistically to make the contact angle of the resulting hydrophobic aerogel ≥150°, and its structure retention rate ≥90% during mortar mixing. The plasma pretreatment activates the aerogel surface, greatly improving the grafting density and strength of the subsequent organosilicon waterproofing agent. This not only gives it superhydrophobic properties with a contact angle ≥150°, effectively blocking water intrusion, but also increases the structure retention rate of the aerogel to over 90% during subsequent mortar mixing through surface strengthening, thus solving the core bottleneck in its application.

[0011] Further, in step (3), the mass ratio of the phase change microcapsules to carbon nanotubes is 1:(0.5~0.7); the co-milling process allows the carbon nanotubes to be uniformly embedded and anchored on the surface of the phase change microcapsule shell, constructing an efficient thermal conductivity pathway. By ball milling, the carbon nanotubes are uniformly embedded and anchored on the phase change microcapsule shell, forming a localized, efficient thermal conductivity pathway based on the microcapsule unit. This not only significantly accelerates the thermal response speed of the phase change material, making its temperature regulation more timely and efficient, but also the reinforcing effect of the carbon nanotubes reduces the breakage rate of the microcapsules during stirring, effectively preventing leakage of the phase change core material.

[0012] Further, in step (5), the biochar powder is obtained by pyrolyzing agricultural waste at 500-700℃ for 2-4 hours in an anaerobic environment, followed by ball milling until the specific surface area reaches 200-400 m². 2 / g prepared. Biochar powder prepared from agricultural waste using a specific process has a well-developed porous structure (specific surface area 200~400m²). 2 The material ( / g) is not only lightweight and has a certain heat insulation property, but it can also adsorb free water, regulate the internal humidity of mortar, and work synergistically with nano-montmorillonite to improve the density and ion exchange capacity of the system, thus having both environmental protection and functional benefits.

[0013] Furthermore, in step (7), the mass ratio of the shape memory polymer emulsion to chitosan is (2~3):1. By controlling the mass ratio of the shape memory polymer emulsion to chitosan at (2~3):1, the two can form an interpenetrating network structure with a moderate crosslinking density during subsequent heating and stirring. This provides the mortar with excellent flexibility and crack bridging ability, while avoiding the brittleness caused by excessive crosslinking, thus achieving the best balance between the toughness and strength of the material.

[0014] This invention also provides an aerogel thermal insulation and waterproof mortar prepared by the above-described method. As a final product, it integrates the advantages of all the above-described preparation processes, possessing comprehensive characteristics of being lightweight and high-strength, providing thermal insulation and waterproofing, intelligent temperature regulation, and good durability, thus offering a high-performance solution for building energy-saving projects.

[0015] Furthermore, the mortar has a thermal conductivity ≤0.030W / (m·K), a water absorption rate ≤3%, a compressive strength ≥5.0MPa, and a bond strength ≥0.8MPa; the mortar has a phase change enthalpy ≥35J / g, and after 50 freeze-thaw cycles, its mass loss rate ≤3% and its compressive strength loss rate ≤8%.

[0016] Further, the mortar comprises the following components in parts by weight: 30-40 parts cement, 5-12 parts hydrophobic aerogel, 6-15 parts interface-modified asphalt powder, 6-15 parts composite phase change thermal conductive material, 18-22 parts blast furnace slag powder, 12-18 parts silica fume, 8-12 parts nano-montmorillonite, 6-9 parts titanium dioxide aerogel powder, 4-7 parts expanded vermiculite, 12-18 parts shape memory polymer emulsion, 4-7 parts chitosan, 4-7 parts biochar powder, 3-6 parts carbon fiber, 1.5-3 parts basalt fiber, 3-5 parts redispersible latex powder, 4-6 parts hydroxypropyl methylcellulose ether, 1.5-2.5 parts polycarboxylate superplasticizer, 3-4 parts water-retaining agent, and 55-65 parts water. This preferred formulation range represents the optimal synergistic range of each component, verified through extensive experimentation. Within this range, each component can fully utilize its own function and generate the best synergistic effect, thereby ensuring that the final product achieves top performance indicators while having optimal cost-effectiveness and process feasibility.

[0017] Compared with the prior art, the present invention has the following beneficial effects: I. This invention utilizes a unique three-stage pretreatment process: "plasma activation-organosilicon hydrophobic modification," "titanium ester coupling agent interface bridging," and "ball milling composite construction of thermally conductive pathways," to construct a stable multiphase interface structure at the molecular level. Plasma treatment generates abundant active sites on the aerogel surface, significantly improving the grafting density and bonding strength of the organosilicon waterproofing agent, forming a durable superhydrophobic interface. The active groups introduced by the titanate coupling agent on the asphalt powder surface can form strong Si-O-Si and Si-O-Ca covalent bonds with cement hydration products. Ball milling composite enables carbon nanotubes and phase change microcapsules to form a stable "core-shell" thermally conductive structure. This multi-level synergistic functional network overcomes the performance limitations of individual components in traditional materials, achieving synergistic optimization of thermal insulation, waterproofing, and mechanical properties.

[0018] II. This invention employs a three-stage process system: "basic framework construction - functional component introduction - intelligent cross-linking curing." First, a strong and tough three-dimensional framework network composed of inorganic matrix, modified asphalt powder, and hybrid fibers is formed under optimized rotation speed. Then, specially treated aerogel and phase change composite materials are introduced under protective rotation speed to ensure uniform dispersion of functional components while maximizing the preservation of their microstructural integrity. Finally, ultrasonic-assisted dispersion and programmed temperature-controlled curing achieve in-situ cross-linking of shape memory polymers and chitosan to form a three-dimensional interpenetrating network. This precise process design ensures that each functional component exerts a synergistic effect under optimal conditions, resulting in optimal material performance.

[0019] Third, this invention is the first to integrate hydrophobic aerogel, interface-modified bitumen powder, composite phase change thermal conductive material, and shape memory polymer system to construct an intelligent material system with temperature adaptive regulation capability. Phase change microcapsules achieve dynamic thermal energy management through solid-liquid phase change, effectively mitigating temperature fluctuations; shape memory polymers undergo reversible phase changes within a specific temperature range, endowing the material with thermal stress adaptive function; hydrophobic aerogel provides a durable and stable thermal insulation barrier; and modified bitumen powder contributes elastic recovery capability and auxiliary waterproofing function. This multi-layered intelligent response mechanism enables the material to autonomously adjust its thermal performance and mechanical state according to environmental changes, achieving integrated functionality of building envelope, including thermal insulation, waterproofing, temperature regulation, and load-bearing capacity. Detailed Implementation

[0020] The specific embodiments are described in detail below, but it should be understood that the scope of protection of the present invention is not limited to the specific embodiments. Unless otherwise specified, the raw materials and reagents used in the examples are commercially available.

[0021] Example 1 A method for preparing an aerogel thermal insulation and waterproof mortar includes the following steps: (1) 12 kg of hydrophilic silica aerogel was placed in a plasma treatment device and treated at 600 W power for 10 min under an argon atmosphere and a pressure of 80 Pa. Then, 1.44 kg of organosilicon waterproofing agent (composed of 0.96 kg of methyltrimethoxysilane and 0.48 kg of hexamethyldisilazane) was sprayed in by atomization and treated at 300 rpm for 15 min to obtain hydrophobic aerogel. (2) Preheat 10kg of 40-mesh waste tire asphalt powder to 80℃, add 0.2kg of titanate coupling agent NDZ-201, and react at 500rpm for 30min to obtain interface modified asphalt powder. (3) 10 kg of phase change microcapsules (core material is paraffin, phase change temperature is 25℃, shell material is polymethyl methacrylate) and 5 kg of carbon nanotubes were ground together in a ball mill at 400 rpm for 45 min to obtain a composite phase change thermal conductive material. (4) Grind 40kg of cement, 20kg of blast furnace slag powder, 15kg of silica fume, 10kg of nano montmorillonite, 8kg of titanium dioxide aerogel powder and 6kg of expanded vermiculite together to 350 mesh to obtain inorganic composite matrix. (5) The inorganic composite matrix obtained in step 4, the interface-modified asphalt powder obtained in step 2, 5 kg of reinforcing fiber (composed of 3 kg of 3 mm long carbon fiber and 2 kg of 2 mm long basalt fiber), and 6 kg of biochar powder (made by ball milling rice husks after anaerobic pyrolysis at 600℃ for 3 h to a specific surface area of ​​300 m²) are combined. 2 (Prepared by mixing / g) at 500rpm for 15min to form the basic skeleton material; (6) Add the hydrophobic aerogel obtained in step 1, the composite phase change thermal conductive material obtained in step 3, 4 kg of redispersible latex powder, and 5 kg of hydroxypropyl methylcellulose ether to the basic skeleton material obtained in step 5, and mix at 150 rpm for 20 min to obtain a uniform dry mix. (7) Prepare a liquid phase by mixing 60 kg of water, 2 kg of polycarboxylate superplasticizer, 3.5 kg of water-retaining agent, 15 kg of shape memory polymer emulsion (polyurethane emulsion with glass transition temperature of 30°C) and 5 kg of chitosan; add the liquid phase to the dry mixture obtained in step 6 at a speed of 60 rpm under the assistance of ultrasonic waves at a frequency of 30 kHz and a power of 300 W, and then heat it to 65°C at a speed of 3°C / min. At this temperature, stir continuously at a speed of 120 rpm for 30 min to obtain the aerogel thermal insulation and waterproof mortar.

[0022] Example 2 A method for preparing an aerogel thermal insulation and waterproof mortar includes the following steps: (1) 5 kg of hydrophilic silica aerogel was placed in a plasma treatment device and treated at 500 W power for 5 min under an argon atmosphere and a pressure of 50 Pa. Then, 0.5 kg of organosilicon waterproofing agent (composed of 0.33 kg of methyltrimethoxysilane and 0.17 kg of hexamethyldisilazane) was sprayed in by atomization and treated at 200 rpm for 10 min to obtain hydrophobic aerogel. (2) Preheat 5 kg of 80 mesh waste tire asphalt powder to 70°C, add 0.075 kg of titanate coupling agent NDZ-201, and react at 400 rpm for 20 min to obtain interface modified asphalt powder. (3) 5 kg of phase change microcapsules (core material is paraffin, phase change temperature is 22℃, shell material is polymethyl methacrylate) and 3 kg of carbon nanotubes are ground together in a ball mill at 300 rpm for 30 min to obtain a composite phase change thermal conductive material. (4) Grind 30kg of cement, 15kg of blast furnace slag powder, 10kg of silica fume, 5kg of nano montmorillonite, 5kg of titanium dioxide aerogel powder and 3kg of expanded vermiculite together to 300 mesh to obtain inorganic composite matrix. (5) The inorganic composite matrix obtained in step 4, the interface-modified asphalt powder obtained in step 2, 2 kg of reinforcing fiber (composed of 1.2 kg of carbon fiber with a length of 2 mm and 0.8 kg of basalt fiber with a length of 1 mm), and 3 kg of biochar powder (made by ball milling wheat straw after anaerobic pyrolysis at 500℃ for 2 h to a specific surface area of ​​200 m²) are combined. 2 (Prepared by mixing / g) at 400rpm for 10min to form the basic skeleton material; (6) Add the hydrophobic aerogel obtained in step 1, the composite phase change thermal conductive material obtained in step 3, 2 kg of redispersible latex powder, and 3 kg of hydroxypropyl methylcellulose ether to the basic skeleton material obtained in step 5, and mix at 100 rpm for 15 min to obtain a uniform dry mix. (7) Prepare a liquid phase by mixing 50 kg of water, 1 kg of polycarboxylate superplasticizer, 2 kg of water-retaining agent, 10 kg of shape memory polymer emulsion (polyurethane emulsion with glass transition temperature of 25°C) and 3 kg of chitosan; add the liquid phase to the dry mixture obtained in step 6 at a speed of 40 rpm under the assistance of ultrasonic waves at a frequency of 20 kHz and a power of 200 W, and then heat it to 60°C at a speed of 2°C / min. At this temperature, stir continuously at a speed of 100 rpm for 20 min to obtain the aerogel thermal insulation and waterproof mortar.

[0023] Example 3 A method for preparing an aerogel thermal insulation and waterproof mortar includes the following steps: (1) 20 kg of hydrophilic silica aerogel was placed in a plasma treatment device and treated at 800 W power for 15 min under an argon atmosphere and a pressure of 100 Pa. Then, 4 kg of organosilicon waterproofing agent (composed of 2.67 kg of methyltrimethoxysilane and 1.33 kg of hexamethyldisilazane) was sprayed in by atomization and treated at 400 rpm for 20 min to obtain hydrophobic aerogel. (2) Preheat 15kg of 40-mesh waste tire asphalt powder to 90℃, add 0.6kg of titanate coupling agent NDZ-201, and react at 600rpm for 40min to obtain interface modified asphalt powder. (3) 15 kg of phase change microcapsules (core material is paraffin, phase change temperature is 28℃, shell material is polymethyl methacrylate) and 8 kg of carbon nanotubes were ground together in a ball mill at 500 rpm for 60 min to obtain a composite phase change thermal conductive material. (4) Grind 50kg of cement, 25kg of blast furnace slag powder, 20kg of silica fume, 15kg of nano montmorillonite, 10kg of titanium dioxide aerogel powder and 8kg of expanded vermiculite together to 400 mesh to obtain inorganic composite matrix. (5) The inorganic composite matrix obtained in step 4, the interface-modified asphalt powder obtained in step 2, 8 kg of reinforcing fiber (composed of 5 kg of 5 mm long carbon fiber and 3 kg of 3 mm long basalt fiber), and 9 kg of biochar powder (made by ball milling corn stalks after anaerobic pyrolysis at 700℃ for 4 h to a specific surface area of ​​400 m²) are combined. 2 (Prepared by mixing / g) at 600rpm for 20min to form the basic skeleton material; (6) Add the hydrophobic aerogel obtained in step 1, the composite phase change thermal conductive material obtained in step 3, 6 kg of redispersible latex powder, and 7 kg of hydroxypropyl methylcellulose ether to the basic skeleton material obtained in step 5, and mix at 200 rpm for 25 min to obtain a uniform dry mix. (7) Prepare a liquid phase by mixing 70 kg of water, 3 kg of polycarboxylate superplasticizer, 5 kg of water-retaining agent, 20 kg of shape memory polymer emulsion (polyurethane emulsion with glass transition temperature of 35°C) and 8 kg of chitosan; add the liquid phase to the dry mixture obtained in step 6 at a speed of 80 rpm under the assistance of ultrasonic waves at a frequency of 40 kHz and a power of 400 W, and then heat it to 70°C at a speed of 4°C / min. At this temperature, stir continuously at a speed of 150 rpm for 40 min to obtain the aerogel thermal insulation and waterproof mortar.

[0024] Comparative Example 1 (Traditional Thermal Insulation Mortar) Preparation method: (1) Prepare 12 kg of ordinary expanded perlite (40-60 mesh) as thermal insulation aggregate; (2) Grind 40kg of cement, 20kg of lime powder, 15kg of quicklime and 10kg of quartz powder together to 350 mesh to obtain inorganic base material; (3) Mix the inorganic base material obtained in step (2), 12kg of expanded perlite, 5kg of reinforcing fiber (composed of 3kg of 3mm long polypropylene fiber and 2kg of 2mm long glass fiber), and 6kg of ordinary wood powder at 500rpm for 15 minutes. (4) Prepare a liquid phase by mixing 60kg water, 2kg polycarboxylate superplasticizer, 3.5kg water-retaining agent, 0.5kg organosilicon waterproofing agent (external additive) and 15kg styrene-acrylic emulsion. Add the liquid phase to the mixture obtained in step (3) at a speed of 60rpm. Stir continuously at a speed of 120rpm for 30 minutes at room temperature to obtain traditional thermal insulation mortar.

[0025] Comparative Example 2 (aerogel hydrophobication treatment omitted) Preparation method: (1) Directly use 12 kg of untreated hydrophilic silica aerogel; (2) Preheat 10kg of 40-mesh waste tire asphalt powder to 80℃, add 0.2kg of titanate coupling agent NDZ-201, and react at 500rpm for 30 minutes to obtain interface modified asphalt powder. (3) 10 kg of phase change microcapsules (core material is paraffin, phase change temperature is 25℃, shell material is polymethyl methacrylate) and 5 kg of carbon nanotubes are ground together in a ball mill at 400 rpm for 45 minutes to obtain a composite phase change thermal conductive material. (4) Grind 40kg of cement, 20kg of blast furnace slag powder, 15kg of silica fume, 10kg of nano montmorillonite, 8kg of titanium dioxide aerogel powder and 6kg of expanded vermiculite together to 350 mesh to obtain inorganic composite matrix. (5) The inorganic composite matrix obtained in step (4), the interface modified asphalt powder obtained in step (2), 5 kg of reinforcing fiber (composed of 3 kg of 3 mm long carbon fiber and 2 kg of 2 mm long basalt fiber), and 6 kg of biochar powder are mixed at 500 rpm for 15 minutes to form the basic skeleton material. (6) Add the untreated aerogel obtained in step (1), the composite phase change thermal conductive material obtained in step (3), 4 kg of redispersible latex powder, and 5 kg of hydroxypropyl methylcellulose ether to the basic skeleton material obtained in step (5), and mix at 150 rpm for 20 minutes to obtain a uniform dry mix. (7) Prepare a liquid phase by mixing 60kg water, 2kg polycarboxylate superplasticizer, 3.5kg water-retaining agent, 15kg shape memory polymer emulsion (polyurethane emulsion with glass transition temperature of 30℃) and 5kg chitosan; add the liquid phase to the dry mixture obtained in step (6) at a speed of 60rpm under the assistance of ultrasonic waves at a frequency of 30kHz and a power of 300W, and then heat it to 65℃ at a speed of 3℃ / min. At this temperature, stir continuously at a speed of 120rpm for 30 minutes to obtain the comparison mortar.

[0026] Comparative Example 3 (interfacial modification of asphalt binder powder omitted) Preparation method: (1) 12 kg of hydrophilic silica aerogel was placed in a plasma treatment device and treated at 600 W power for 10 minutes under an argon atmosphere and a pressure of 80 Pa. Then, 1.44 kg of organosilicon waterproofing agent (composed of 0.96 kg of methyltrimethoxysilane and 0.48 kg of hexamethyldisilazane) was sprayed in by atomization and treated at 300 rpm for 15 minutes to obtain hydrophobic aerogel. (2) Directly use 10kg of untreated 40-mesh waste tire asphalt powder; (3) 10 kg of phase change microcapsules (core material is paraffin, phase change temperature is 25℃, shell material is polymethyl methacrylate) and 5 kg of carbon nanotubes are ground together in a ball mill at 400 rpm for 45 minutes to obtain a composite phase change thermal conductive material. (4) Grind 40kg of cement, 20kg of blast furnace slag powder, 15kg of silica fume, 10kg of nano montmorillonite, 8kg of titanium dioxide aerogel powder and 6kg of expanded vermiculite together to 350 mesh to obtain inorganic composite matrix. (5) The inorganic composite matrix obtained in step (4), the untreated asphalt powder obtained in step (2), 5 kg of reinforcing fiber (composed of 3 kg of 3 mm long carbon fiber and 2 kg of 2 mm long basalt fiber), and 6 kg of biochar powder are mixed at 500 rpm for 15 minutes to form the basic skeleton material. (6) Add the hydrophobic aerogel obtained in step (1), the composite phase change thermal conductive material obtained in step (3), 4 kg of redispersible latex powder, and 5 kg of hydroxypropyl methylcellulose ether to the basic skeleton material obtained in step (5), and mix at 150 rpm for 20 minutes to obtain a uniform dry mix. (7) Prepare a liquid phase by mixing 60kg water, 2kg polycarboxylate superplasticizer, 3.5kg water-retaining agent, 15kg shape memory polymer emulsion (polyurethane emulsion with glass transition temperature of 30℃) and 5kg chitosan; add the liquid phase to the dry mixture obtained in step (6) at a speed of 60rpm under the assistance of ultrasonic waves at a frequency of 30kHz and a power of 300W, and then heat it to 65℃ at a speed of 3℃ / min. At this temperature, stir continuously at a speed of 120rpm for 30 minutes to obtain the comparison mortar.

[0027] Comparative Example 4 (Changing the mixing process sequence) Preparation method: (1) 12 kg of hydrophilic silica aerogel was placed in a plasma treatment device and treated at 600 W power for 10 minutes under an argon atmosphere and a pressure of 80 Pa. Then, 1.44 kg of organosilicon waterproofing agent (composed of 0.96 kg of methyltrimethoxysilane and 0.48 kg of hexamethyldisilazane) was sprayed in by atomization and treated at 300 rpm for 15 minutes to obtain hydrophobic aerogel. (2) Preheat 10kg of 40-mesh waste tire asphalt powder to 80℃, add 0.2kg of titanate coupling agent NDZ-201, and react at 500rpm for 30 minutes to obtain interface modified asphalt powder. (3) 10 kg of phase change microcapsules (core material is paraffin, phase change temperature is 25℃, shell material is polymethyl methacrylate) and 5 kg of carbon nanotubes are ground together in a ball mill at 400 rpm for 45 minutes to obtain a composite phase change thermal conductive material. (4) Grind 40kg of cement, 20kg of blast furnace slag powder, 15kg of silica fume, 10kg of nano montmorillonite, 8kg of titanium dioxide aerogel powder and 6kg of expanded vermiculite together to 350 mesh to obtain inorganic composite matrix. (5) Mix all raw materials at once: Mix the inorganic composite base material obtained in step (4), the interface modified asphalt powder obtained in step (2), the hydrophobic aerogel obtained in step (1), the composite phase change thermal conductive material obtained in step (3), 5 kg of reinforcing fiber, 6 kg of biochar powder, 4 kg of redispersible latex powder, and 5 kg of hydroxypropyl methylcellulose ether at 500 rpm for 20 minutes to obtain a mixture; (6) Prepare a liquid phase by mixing 60kg water, 2kg polycarboxylate superplasticizer, 3.5kg water-retaining agent, 15kg shape memory polymer emulsion (polyurethane emulsion with glass transition temperature of 30℃) and 5kg chitosan; add the liquid phase to the mixture obtained in step (5) at a speed of 60rpm under the assistance of ultrasonic waves at a frequency of 30kHz and a power of 300W, and then heat it to 65℃ at a speed of 3℃ / min. Stir continuously at a speed of 120rpm for 30 minutes at this temperature to obtain the comparison mortar.

[0028] Comparative Example 5 (using traditional materials as substitutes) Preparation method: (1) Use 12kg of ordinary vitrified microspheres (to replace aerogel) as thermal insulation aggregate; (2) Use 10 kg of ordinary rubber powder (instead of asphalt rubber powder); (3) Grind 40kg of cement, 20kg of blast furnace slag powder, 15kg of silica fume, 10kg of fly ash (to replace nano montmorillonite), 8kg of ordinary silica powder (to replace titanium dioxide aerogel powder), and 6kg of expanded perlite (to replace expanded vermiculite) together to 350 mesh to obtain inorganic base material; (4) Mix the inorganic base material obtained in step (3), the ordinary rubber powder obtained in step (2), 5 kg of ordinary polypropylene fiber (single type of fiber), and 6 kg of ordinary wood chip powder at 500 rpm for 15 minutes. (5) Add the vitrified microspheres obtained in step (1), 4 kg of redispersible latex powder, and 5 kg of hydroxypropyl methylcellulose ether to the mixture obtained in step (4), and mix at 150 rpm for 20 minutes to obtain the mixture; (6) Prepare a liquid phase by mixing 60kg water, 2kg polycarboxylate superplasticizer, 3.5kg water-retaining agent, 15kg ordinary acrylic emulsion (to replace shape memory polymer emulsion) and 5kg ordinary starch (to replace chitosan). Add the liquid phase to the mixture obtained in step (5) at 60rpm and stir continuously at 120rpm for 30 minutes at room temperature to obtain the comparison mortar.

[0029] The performance of Examples 1-3 and Comparative Examples 1-5 was compared and tested as follows: 1. Thermal conductivity Test standard: GB / T 10294 "Determination of Steady-State Thermal Resistance and Related Properties of Thermal Insulation Materials - Protective Hot Plate Method" Method Summary: The sample is prepared with dimensions of 300mm × 300mm × 30mm. Under steady-state heat flow conditions, the heat flow through the sample and the temperature difference between its two surfaces are measured, and the thermal conductivity is calculated. The test temperature is 25±2℃.

[0030] 2. Water absorption rate Test standard: GB / T 5486 "Test Methods for Inorganic Rigid Thermal Insulation Products" Method summary: After drying the sample to constant weight, weigh the initial mass, immerse it in water at 20±5℃ for 72 hours, remove it, wipe off the surface moisture, weigh it again, and calculate the percentage increase in mass.

[0031] 3. Compressive strength Test standard: GB / T 17671 "Test method for strength of cement mortar (ISO method)" Method summary: Prepare 40mm×40mm×160mm prism specimens, cure under standard conditions for 28 days, and use a pressure testing machine to load at a rate of 2400±200N / s, and record the maximum load at which the specimen fails.

[0032] 4. Bond strength Test standard: JG / T 24 "Synthetic Resin Emulsion Sand-textured Architectural Coatings" Method summary: Prepare bonding specimens of mortar and concrete substrate, and use a tensile testing machine to stretch them at a rate of 5±1 mm / min to measure the maximum tensile force at which the bonding interface fails.

[0033] 5. Phase transition enthalpy Test standard: GB / T 19466.3 Differential Scanning Calorimetry (DSC) for Plastics - Part 3 Method Summary: Differential scanning calorimetry (DSC) was used to perform temperature rise and fall scans at a rate of 5 °C / min under a nitrogen atmosphere. The phase transition enthalpy was calculated by analyzing the DSC curves.

[0034] 6. Contact angle Test standard: GB / T 30447 "Method for measuring the contact angle of nanofilms" Method summary: Using a contact angle measuring instrument, 2 μL of distilled water was dropped onto the sample surface, and the liquid-solid interface angle was measured using an image analysis system.

[0035] 7. Freeze-thaw cycle performance Test standard: GB / T 50082 "Standard for Test Methods of Long-Term Performance and Durability of Ordinary Concrete" Method Summary: After immersing the specimen in water for 48 hours, freeze it at -20±2℃ for 4 hours, and then thaw it in water at 20±2℃ for 4 hours, constituting one cycle. Record the mass loss and strength change after the specified number of cycles.

[0036] 8. Aerogel structure retention rate Test method: The microstructure of aerogel in mortar was observed using a scanning electron microscope (SEM). The proportion of intact aerogel particles was calculated using image analysis software, and the retention rate was obtained by comparing it with the original aerogel structure.

[0037] All tests were conducted in a standard laboratory environment (temperature 23±2℃, relative humidity 50±5%), and each set of data is the average of 5 specimens.

[0038] The test data is shown in the table below: Thermal conductivity (W / (m·K)) 0.026 0.029 0.024 0.068 0.045 0.042 0.038 0.062 Water absorption rate (%) 2.5 3.2 2.1 21.3 15.8 9.6 6.8 18.5 Compressive strength (MPa) 5.8 5.1 6.2 2.3 3.5 3.1 4.2 2.8 Bond strength (MPa) 0.85 0.78 0.89 0.32 0.51 0.45 0.63 0.41 Phase transition enthalpy (J / g) 38.2 35.8 39.5 - 36.5 37.1 36.8 - Contact angle (°) 162 155 165 95 108 145 152 102 50 freeze-thaw cycles mass loss rate (%) 2.1 2.8 1.8 18.5 12.3 8.7 5.6 15.2 Strength loss rate after 50 freeze-thaw cycles (%) 6.8 8.2 5.9 42.3 28.5 22.1 15.3 35.8 Aerogel structure retention rate (%) 92 88 94 - 65 88 78 - Analyzing the data in the table, we can obtain: 1. The thermal conductivity of the examples (0.024~0.029 W / (m·K)) is much lower than that of all comparative examples, especially Comparative Example 1 (0.068) and Comparative Example 5 (0.062), proving that aerogel can significantly improve the thermal insulation effect when replacing traditional insulating aggregates. Comparative Example 2, because its aerogel was not hydrophobically treated, has a significantly higher thermal conductivity (0.045) than Example 1, indicating that hydrophobic treatment is crucial for maintaining the thermal insulation performance of aerogel.

[0039] 2. The water absorption rate of the examples (2.1~3.2%) was much lower than that of all comparative examples, especially Comparative Example 1 (21.3%) and Comparative Example 5 (18.5%). Comparative Example 2, due to its untreated aerogel, had a water absorption rate as high as 15.8%, demonstrating the necessity of hydrophobic treatment. Comparative Example 3, due to its unmodified asphalt powder and poor interfacial bonding, also had a significantly higher water absorption rate (9.6%) than Example 1.

[0040] 3. The compressive strength (5.1~6.2MPa) and bond strength (0.78~0.89MPa) of the examples were significantly higher than those of the comparative examples. The mechanical properties of Comparative Example 3 (without asphalt powder modification) decreased significantly, demonstrating the importance of interface modification. The performance of Comparative Example 4 (with a changed mixing order) was also lower than that of Example 1, demonstrating that the staged mixing process plays a crucial role in protecting the aerogel structure and achieving component synergy.

[0041] 4. After 50 freeze-thaw cycles, the mass loss rate (1.8~2.8%) and strength loss rate (5.9~8.2%) of the examples were much lower than those of the comparative examples. The traditional mortar in Comparative Example 1 suffered a strength loss of up to 42.3% after freeze-thaw cycles, which completely failed to meet the durability requirements.

[0042] 5. Although Comparative Examples 2, 3, and 4 have phase change temperature regulation function (phase change enthalpy 36-37 J / g), they are significantly inferior to the Examples in other key performance aspects due to their respective technical defects, which proves the necessity of the systematic solution of the present invention.

[0043] In summary, through systematic comparative experiments, the innovativeness of this invention in terms of component selection, material modification, and process design, as well as the resulting breakthrough in overall performance, have been fully demonstrated. The synergistic effect among the various technical features is significant; the absence or alteration of any single feature will lead to a significant decrease in overall performance.

[0044] It should be understood that the above embodiments are only for illustrating the technical concept and features of the present invention, and are intended to enable those skilled in the art to understand the content of the present invention and implement it accordingly. It should not be considered that the specific implementation of the present invention is limited to these descriptions. For those skilled in the art, several simple deductions or substitutions can be made without departing from the concept of the present invention. All equivalent changes or modifications made in accordance with the spirit and essence of the present invention should be covered within the protection scope of the present invention.

Claims

1. A method for preparing aerogel thermal insulation and waterproof mortar, characterized in that, Includes the following steps: (1) Place 5-20 parts of hydrophilic silica aerogel in a plasma treatment device, and treat it at 500-800W power for 5-15 minutes under an argon atmosphere and a pressure of 50-100Pa. Then, spray in 10-20% of the aerogel mass of organosilicon waterproofing agent and treat it at a speed of 200-400rpm for 10-20 minutes to obtain hydrophobic aerogel. The organosilicon waterproofing agent is a mixed solution of methyltrimethoxysilane and hexamethyldisilazane in a mass ratio of 2:

1. (2) Preheat 5-15 parts of 40-80 mesh waste tire asphalt powder to 70-90℃, add 2-4% of titanate coupling agent NDZ-201 by weight of the powder, and react at 400-600 rpm for 20-40 min to obtain interface modified asphalt powder. (3) Grind 5-15 parts of phase change microcapsules and 3-8 parts of carbon nanotubes together in a ball mill at a speed of 300-500 rpm for 30-60 min to obtain a composite phase change thermal conductive material; the core material of the phase change microcapsules is paraffin wax, the phase change temperature is 22-28℃, and the shell material is polymethyl methacrylate. (4) Grind 30-50 parts of cement, 15-25 parts of blast furnace slag powder, 10-20 parts of silica fume, 5-15 parts of nano montmorillonite, 5-10 parts of titanium dioxide aerogel powder, and 3-8 parts of expanded vermiculite together to 300-400 mesh to obtain an inorganic composite matrix. (5) The inorganic composite matrix obtained in step (4), the interface-modified asphalt powder obtained in step (2), 2-8 parts of reinforcing fiber, and 3-9 parts of biochar powder are mixed at a speed of 400-600 rpm for 10-20 minutes to form a basic skeleton material; the reinforcing fiber is a hybrid fiber system composed of carbon fiber with a length of 2-5 mm and basalt fiber with a length of 1-3 mm in a mass ratio of (1.5-2.5):

1. (6) Add the hydrophobic aerogel obtained in step (1), the composite phase change thermal conductive material obtained in step (3), 2-6 parts of redispersible latex powder, and 3-7 parts of hydroxypropyl methylcellulose ether to the basic skeleton material obtained in step (5), and mix at 100-200 rpm for 15-25 min to obtain a uniform dry mix. (7) Prepare a liquid phase by mixing 50-70 parts of water, 1-3 parts of polycarboxylate superplasticizer, 2-5 parts of water-retaining agent, 10-20 parts of shape memory polymer emulsion, and 3-8 parts of chitosan; add the liquid phase to the dry mixture obtained in step (6) at a speed of 40-80 rpm under the assistance of ultrasound at a frequency of 20-40 kHz and a power of 200-400 W, and then heat it to 60-70 ℃ at a speed of 2-4 ℃ / min, and stir it continuously at a speed of 100-150 rpm for 20-40 min at this temperature to obtain the aerogel thermal insulation and waterproof mortar; the shape memory polymer emulsion is a polyurethane emulsion with a glass transition temperature of 25-35 ℃.

2. The preparation method according to claim 1, characterized in that: In step (1), the plasma treatment and the modification of the organosilicon waterproofing agent work synergistically to make the contact angle of the resulting hydrophobic aerogel ≥150° and its structure retention rate ≥90% during the mortar mixing process.

3. The preparation method according to claim 1, characterized in that: In step (3), the mass ratio of the phase change microcapsule to the carbon nanotube is 1:(0.5~0.7); the co-grinding makes the carbon nanotube uniformly embedded and anchored on the surface of the phase change microcapsule shell, thus constructing an efficient heat conduction pathway.

4. The preparation method according to claim 1, characterized in that: In step (5), the biochar powder is obtained by pyrolyzing agricultural waste at 500-700℃ for 2-4 hours in an anaerobic environment, followed by ball milling until the specific surface area reaches 200-400 m². 2 / g is prepared.

5. The preparation method according to claim 1, characterized in that: In step (7), the mass ratio of the shape memory polymer emulsion to chitosan is (2~3):

1.

6. An aerogel thermal insulation and waterproof mortar prepared by any one of claims 1 to 5.

7. The aerogel thermal insulation and waterproof mortar according to claim 6, characterized in that: The mortar has a thermal conductivity ≤0.030W / (m·K), a water absorption rate ≤3%, a compressive strength ≥5.0MPa, and a bond strength ≥0.8MPa.

8. The aerogel thermal insulation and waterproof mortar according to claim 6, characterized in that: The mortar has a phase change enthalpy of ≥35J / g, and after 50 freeze-thaw cycles, its mass loss rate is ≤3% and its compressive strength loss rate is ≤8%.

9. The aerogel thermal insulation and waterproof mortar according to claim 6, characterized in that, The product comprises the following components in parts by weight: 30-40 parts cement, 5-12 parts hydrophobic aerogel, 6-15 parts interface-modified asphalt powder, 6-15 parts composite phase change thermal conductive material, 18-22 parts blast furnace slag powder, 12-18 parts silica fume, 8-12 parts nano-montmorillonite, 6-9 parts titanium dioxide aerogel powder, 4-7 parts expanded vermiculite, 12-18 parts shape memory polymer emulsion, 4-7 parts chitosan, 4-7 parts biochar powder, 3-6 parts carbon fiber, 1.5-3 parts basalt fiber, 3-5 parts redispersible latex powder, 4-6 parts hydroxypropyl methylcellulose ether, 1.5-2.5 parts polycarboxylate superplasticizer, 3-4 parts water-retaining agent, and 55-65 parts water.

Citation Information

Patent Citations

  • Nano-additive agent modified high-strength wall self-thermal insulation material and preparing method thereof

    CN101318796A

  • Inorganic insulation mortar based on hydrophobic aerogel and preparation method thereof

    CN107032679A